PENERAPAN MEDIA BIG BOOK DALAM MENINGKATKAN HASIL BELAJAR BAHASA ARAB KELAS IV - Siti Nurohmah; Nanang Kosim; Dede Rohaniawati (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
This study aims to determine student learning outcomes in Arabic subjects before the application of Big Book media, the process of applying Big Book media and student learning outcomes after the application of Big Book media in class IV MI Naelushibyan. The research method used is classroom action research through four repetitive stages of planning, implementation, observation or observation, and reflection. The object of research was 15 students. The research instrument consisted of a teacher activity observation sheet, a student activity observation sheet and a written test. Data collection techniques use observation and test techniques. The results obtained from this study are the learning outcomes of students in the pre cycle get an average score of 53. The first cycle obtained the average value of teacher activity 72.2% and cycle II obtained an average value of 94.4%. Student activity in cycle I obtained an average value of 69.21% and cycle II obtained an average value of 91.07%. Student learning outcomes in cycle I obtained an average value of 77, cycle II obtained an average value of 83.6. It can be concluded that Big Book media can improve student learning outcomes.